ASPEK HUKUM PERAN WAKAF TUNAI PADA MASA PANDEMI COVID 19 - Sulistiani, Siska Lis; Nurrachmi, Intan; Bayuni, Eva Misfah (UI Scholars Hub, 2021)
The development of cash waqf in Indonesia in the past 10 years is of particular concern. With the law No. 41 of 2004 concerning endowments became the initial foothold in the development of forms of cash endowments, including endowments of money, endowments sukuk, endowments of Islamic insurance policies and others. Of all the innovations of this waqf because waqf has more flexible properties to be able to make new breakthroughs that fit the needs of the times without reducing the essence of the waqf. The legal aspect of developing cash waqf is important because it will affect its position and its validity as an endowment asset. This research is a normative juridical study, which uses library research as a method of collecting data and analyzed through descriptive analytical methods, so that innovation in the form of cash waqf in Indonesia has a strong legal basis as a basis for its operation in society.